Startup CEO a field guide to scaling up your business - Blumberg, Matt; Hindi, Hanny (Startup revolution, 2013)
A definitive book for any CEO first time or otherwise of a high-growth company While big company CEOs are usually groomed for the job for years, startup CEOs aren't and they're often young and relatively inexperienced in business in general.